The use of ICT during covid-19: a study of Chinese independent high school English teachers’ readiness and challenges - Bong, Lelia Myriam Siu Mien (2022)
With the emergence of Emergency Remote Teaching in Malaysia during the pandemic, government schools or tertiary institution’s teachers’ readiness for ICT use is well-researched. However, the situation in Chinese Independent High School (CIHS) may suggest a different outcome. A study was conducted to explore the CIHS English teachers’ readiness level and challenges faced in using ICT tools during the Emergency Remote Teaching. The participants consist of 27 teachers across CIHSs from Sarawak, Malaysia in this mixed-method study. A descriptive analysis was performed on the questionnaire survey while a thematic analysis was done on the interview data. Following these, the survey found that teachers obtained very high levels of knowledge in ICT while the readiness level for ICT use was at a high level. Overall, the respondents held positive attitudes towards the use of ICT. On the other hand, the interview data identified four main scopes of challenges faced by the teachers: classroom management, inadequate ICT facilities and conducive environment, lack of user-friendly platforms as well as the emotional aspect. Among which, student engagement and poor internet connection were the primary issues. The research is significant in understanding the language teaching situation in Malaysian CIHSs. Stakeholders should arrange for frequent trainings that incorporate pedagogical aspects or provide manuals to increase teacher’s readiness levels in using ICT. Then, the management should also look into providing fundings for better quality gadgets to achieve effective teaching. Future studies may employ a similar study design involving a larger group of participants for concrete results. Other studies may also consider CIHS’ student readiness.